The role of the Iraqi negotiator in activating water diplomacy... managing the water file with Turkey - Hussein, Marwa Ali (The International and Political Journal, 2025)
Abstract: The water issue is one of the most prominent strategic issues in Iraqi-Turkish relations. Iraq relies primarily on the Tigris and Euphrates rivers, which originate in Turkey. With the increase in Turkish water projects, such as the Ilisu and others, Iraq’s water share has declined, leading to serious environmental and agricultural challenges. Under these circumstances, negotiators face numerous difficulties, such as Turkey’s intransigence, Iraq’s weak negotiating position, and the absence of binding agreements. To achieve success in water negotiations, Iraq requires an integrated approach that combines diplomacy and sustainable strategic planning. Therefore, Iraqi negotiators must play a pivotal role in managing this issue by activating water diplomacy to protect Iraq’s water rights and secure sustainable resources for the country. This is achieved by strengthening bilateral dialogue, adhering to international laws, and engaging regional and international organizations. Iraq can also utilize economic and political tools and link the water issue to trade cooperation. This can be achieved by activating water negotiations and utilizing the numerous pressure tools available to it in its negotiations with Turkey to manage the water issue.